Education and humanism linking autonomy and humanity - Veugelers, Wiel (Moral development and citizenship education., 2011)
Human beings have the possibility to give meaning to their lives and to create coherence in experiences. Present-day humanism strongly focuses on personal development in relation to others. It is this tension between personal development and advancement of humanization, that is creating the opportunities for the personal development of every world citizen. Humanism is about personal autonomy, moral responsibility, and about solidarity with humanity. The tension between autonomy and social involvement is the core of humanism. Education can support persons in their moral and personal identity development. The authors brought together in this book all address issues of developing autonomy and humanity in educational practices. All the chapters try to link theory and practice. They either make theoretical ideas more practical or they use practical experiences and concerns to rethink theoretical notions. Together the chapters in the book give a broad overview of theoretical foundations, concrete research, and practices in education. The book shows a diversity that can inspire scholars and practitioners in further developing their perspectives. Creating meaning is an essential part of all education. Focusing on the linking of autonomy and humanity is the humanist perspective in it.